2020
DOI: 10.1186/s12889-020-09721-2
|View full text |Cite|
|
Sign up to set email alerts
|

A survival analysis of COVID-19 in the Mexican population

Abstract: Background At present, the Americas report the largest number of cases of COVID-19 worldwide. In this region, Mexico is the third country with most deaths (20,781 total deaths). A sum that may be explained by the high proportion of people over 50 and the high rate of chronic diseases. The aim of this analysis is to investigate the risk factors associated with COVID-19 deaths in Mexican population using survival analysis. Methods Our analysis includes all confirmed COVID-19 cases contained in the dataset publ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
4
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 25 publications
12
63
4
9
Order By: Relevance
“…Two thirds (90/131; 69%) of the patients admitted in De Martini hospital during the study period were males, with mean age of 58.2 years for males and 56.9 years for females. These findings are consistent with other studies in Vietnam [6] and China [8] which suggest a slight gender difference in hospitalized patients with COVID-19. The signs and symptoms by age group and sex in our study do not differ from those reported in studies outside of Africa [8,9,14]; however there are no comparable data from African settings, especially in sub-Saharan African countries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two thirds (90/131; 69%) of the patients admitted in De Martini hospital during the study period were males, with mean age of 58.2 years for males and 56.9 years for females. These findings are consistent with other studies in Vietnam [6] and China [8] which suggest a slight gender difference in hospitalized patients with COVID-19. The signs and symptoms by age group and sex in our study do not differ from those reported in studies outside of Africa [8,9,14]; however there are no comparable data from African settings, especially in sub-Saharan African countries.…”
Section: Discussionsupporting
confidence: 93%
“…The use of vasopressors and inotropes did not reduce the risk of death, as patient received such treatment have very low probability of survival, and the adjusted hazard of death is 6.24 (95%CI: 3.55,10.99) compared to those who were not given the treatment (calculation not shown). Another study has reported similar results [8].…”
Section: Discussionsupporting
confidence: 74%
“…Besides, about half of the patients infected with SARS-CoV-2 had a chronic underlying disease, particularly cardiovascular and cerebrovascular disease, and diabetes, similar to MERS-CoV (Badawi et al ., 2020). The risk of death at any time during follow-up was significantly higher in men, individuals in the older age group, with chronic kidney disease, and people who were hospitalized (Salinas-Escudero et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A significant association was found among the overall comparisons between the analysis of survival and length of hospitalization of COVID-19 patients. In a study conducted by Thai et al, It was shown that the mean duration of hospital stay was 21 (IQR: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] days. The multivariable Cox regression model shows that age, place of residence, and contamination source are significantly associated with longer duration of stay (Thai et al, 2020).…”
Section: Survival Analysismentioning
confidence: 99%
“…It was highlighted that in the original article [ 1 ] the letter χ was missing in footnote b of Table 1 and on the equation in the Results section on page 5. This Correction article shows the correct Table 1 footnotes and the correct equation.…”
mentioning
confidence: 99%